2016
DOI: 10.1155/2016/2616539
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Betatrophin and Irisin Are Not Associated with Pancreaticβ-Cell Function in Previously Diagnosed Type 2 Diabetes Mellitus Patients

Abstract: Betatrophin and irisin are two recently identified hormones which may participate in regulating pancreatic β-cell function. However, the associations of these two hormones with β-cell function remain unclear. The present study aims to demonstrate the associations of circulating betatrophin and irisin levels with β-cell function, assessed by the area under the curve (AUC) of C-peptide, and the possible correlation between these two hormones in previously diagnosed type 2 diabetes mellitus (T2DM) patients. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
3
23
1
3
Order By: Relevance
“…However, the direct effect of irisin on insulin is not fully understood. Some reports suggested that irisin is not correlated with β-cell function (HOMA-β), fasting C-peptide, or fasting insulin levels [34]. Nevertheless, it is notable that irisin was significantly associated with MetS, although irisin was not correlated with insulin and HOMA-IR in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…However, the direct effect of irisin on insulin is not fully understood. Some reports suggested that irisin is not correlated with β-cell function (HOMA-β), fasting C-peptide, or fasting insulin levels [34]. Nevertheless, it is notable that irisin was significantly associated with MetS, although irisin was not correlated with insulin and HOMA-IR in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…In humans, irisin is positively associated with circulating levels of insulin and HOMA of β-cell function (HOMA-β) in individuals with normal glucose tolerance ( n = 254), indicating that irisin might be involved in the regulation of β-cell function 90 . However, in another study, irisin correlated neither with HOMA-β nor with fasting C-peptide or fasting insulin levels 91 .…”
Section: Effects On Glucose Homeostasismentioning
confidence: 85%
“…The concentration of RBP-4 was found to be elevated in obesity and type 2 DM, MetS and CVD (5). Many authors found that RBP-4 levels were associated with MetS parameters and HOMA-IR, the duration of diabetes and carotid atherosclerosis as determined by CIMT (26)(27)(28)(29). There are conflicting results about the association of RBP-4 and CRP levels, probably due to methodological differences (30,31).…”
Section: Discussionmentioning
confidence: 99%